Generalizability of the Maximum Proportional Recovery Rule to Visuospatial Neglect Early Poststroke. (April 2017) - Winters, Caroline; van Wegen, Erwin E. H.; Daffertshofer, Andreas; Kwakkel, Gert
Background and objective . Proportional recovery of upper-extremity motor function and aphasia after stroke may suggest common mechanisms for spontaneous neurobiological recovery. This study aimed to investigate if the proportional recovery rule also applies to visuospatial neglect (VSN) in right-hemispheric first-ever ischemic stroke patients and explored the possible common underlying mechanisms. Methods . Patients with upper-limb paresis and VSN were included. Recovery defined as the change in Letter Cancellation Test (LCT) score at ~8 days and 6 months poststroke. Potential recovery defined as LCTmax -LCTinitial = 20 − LCTinitial . Hierarchical clustering separated fitters and nonfitters of the prediction rule. A cutoff value on LCTmax -LCTinitial was determined. The change in LCT and Fugl-Meyer Assessment Upper Extremity was expressed as a percentage of the total possible score to investigate the communality of proportional recovery. Results . Out of 90 patients, 80 displayed proportional recovery of VSN (ie, "fitters, " 0.97; 95% CI = 0.82-1.12). All patients who did not follow the prediction rule for VSN (ie, "nonfitters") had ≥15 missing O's at baseline and failed to show proportional recovery of the upper limb. Conclusions . This study shows that the proportional recovery rule also applies to patients with VSN poststroke. Patients who fail to show proportional recovery of VSN are the same patients who fail to show proportional recovery of the upper limb. These findings support the idea of common intrahemispheric mechanisms underlying spontaneous neurobiological recovery in the first months poststroke. Future studies should investigate the prognostic clinical and neurobiological markers of these subgroups.